2015
DOI: 10.1016/j.apsoil.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of soil microbial biomass and its relationships with edaphic, vegetational and climatic factors in the Three-River Headwaters region on Qinghai-Tibetan Plateau

Abstract: a b s t r a c tThis study aims to investigate the level of soil microbial biomass (MB) and analyze the relationships between soil MB and edaphic, vegetational and climatic factors at high elevation sites (>3000 m). We collected soil samples from 0 to 10 cm soil depth in 259 plots at 55 sites across 6 biomes in Three-River Headwaters (TRH) region at 3280-5127 m elevation. Soil microbial biomass carbon and nitrogen (MBC and MBN) were measured with the chloroform fumigation-extraction method. Multivariate stepw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 68 publications
5
13
0
Order By: Relevance
“…Our mean Nmicr/TN in the topsoil (3.4%) was higher than that reported by Shen R. et al (2015) (2.5%), which instead was more similar to the mean value we found in the subsoil (2.9%). On the other hand, our mean Cmicr/TOC ratios in the topsoil (2.1%) and in the subsoil (2.5%) were both higher than those measured in the topsoil (1.1%) by Shen R. et al (2015) in the Tibetan Plateau (Table 4, part b).…”
Section: Depth Variability Of N and C Formssupporting
confidence: 77%
See 1 more Smart Citation
“…Our mean Nmicr/TN in the topsoil (3.4%) was higher than that reported by Shen R. et al (2015) (2.5%), which instead was more similar to the mean value we found in the subsoil (2.9%). On the other hand, our mean Cmicr/TOC ratios in the topsoil (2.1%) and in the subsoil (2.5%) were both higher than those measured in the topsoil (1.1%) by Shen R. et al (2015) in the Tibetan Plateau (Table 4, part b).…”
Section: Depth Variability Of N and C Formssupporting
confidence: 77%
“…Soil nitrogen (N) and carbon (C) cycling in alpine tundra ecosystem have been primarily investigated in the topsoil (0-10 cm), while the underlying subsoil has received much less attention (e.g. Fisk and Schmidt, 1996;Jaeger et al, 1999;Lipson et al, 1999;Shen C. et al, 2015;Shen R. et al, 2015). Even pedoclimatic factors, such as soil temperature and soil moisture, have been typically measured in the surface soil layer but not lower (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The CF + PV treatment significantly increased the diversity of bacteria (Shannon index; Table ). Previous studies have indicated that the application of organic material increases soil bacterial diversity compared with controls (Shen, Xu, Li, Zhao, & Sheng, ; Mabuhay, Nakagoshi, & Isagi, ). The bacterial diversity of soil treated with manure was not significantly higher than the control in our experiment.…”
Section: Discussionmentioning
confidence: 95%
“…Following an assumption similar to that made by Budyko (1974), actual evapotranspiration can be estimated as follows (Shen et al 2015):…”
Section: Methodsmentioning
confidence: 99%